The establishment of PCR amplification, cloning, and sequencing of bovine herpesvirus 1 (BHV-1) glycoprotein D gene isolated in Indonesia - Eko Agus Srihanto; Tri Untari; Michael Haryadi Wibowo; Koichi Akiyama; Widya Asmara; Dewi Noor Hidayati (Indonesian Journal of Biotechnology, 2019)
Considering the increasing incidence of infectious bovine rhinotracheitis (IBR) in Indonesia, it was necessary to conduct a more in-depth study of bovine herpesvirus-1 (BHV-1) as the causative agent of IBR disease. Previous research reports indicate that the BHV-1 subtypes found in Indonesia are subtype 1.1. Currently, IBR field case detection in Indonesia still uses the serological method (ELISA), which has the potential to give false positive results and cannot explain the virus subtype. Other detection methods, such as viral isolation, take longer and require adequate resources. This study aimed to determine the BHV-1 subtypes of Indonesian isolates using molecular techniques. Nested PCR using two pairs of primers was successfully used to amplify the glycoprotein D (gD) gene. The gD gene fragment was cloned into the pGEM-T plasmid. Analysis of the gD gene sequence was subsequently carried out to determine the BHV-1 character of the Indonesian isolates. The results indicated that the isolates were different from the previous isolates, and had similarities (100%) with subtype 1.2 strain SP1777 and SM023.